"Cementación de postes de fibra” revisión bibliográfica - Adriana Denisse, Erazo Conde (2020)
Carrying out a quality clinical cementation procedure during the placing of the post is crucial, due to the development of new cementation systems that, in combination of adhesive systems and surface adaptation processes, provide retention of the post and therefore of the stump in the final restoration. This research is focused on the cementation of fiber posts, through the bibliographic review to fulfill the main objective that is to know, characterize and classify the most used cements during fiber post cementation, with an approach that allows the professional optimizing time and resources to achieve a quality treatment. Considering the research topic, the determined sample was of a non-probabilistic intentional type made up of 51 scientific articles from different scientific journals found in different databases such as Science Direct, Cochrane, Medline, and Pubmed, which to be selected met important characteristics such as to have an Average Count Citation greater than 1.5 or to have a valid impact factor Scimago Journal Ranking and to be within the study time that was between 2010 to 2020. As a documentary-type study, it was done through a comparative meta-analysis chart, which facilitated the comparison and study of each of the articles selected in this investigation, thus obtaining the following results, the most used cements for the placement of fiber posts are the dual-curing resinous cements, due to their double activation, which provide adhesion to the dental substrate in the same way, self-adhesive or self-etching cements, simplifying their placing.